PENINGKATAN PENGETAHUAN DAN KETERAMPILAN PEMULIHAN GIZI BAGI KADER POSYANDU DAN IBU BALITA: Improvement of Nutrition Recovery Knowledges and Skills for Posyandu Cadres and Child Mothers - Riyanto Riyanto; Choirun Nissa (LPPM - STIKES Pemkab Jombang, 2019)
Data from Kepanjen Health Center in Malang Regency in 2017, especially in the Cempokomulyo village, shows that 5.3% of children under five suffer from severe malnutrition and 3.5% suffer from malnutrition. While in the Jatirejoyoso village shows that 3.4% of toddlers experience malnutrition. One of the factors that influence the incidence of malnutrition is the lack of access to care and information for mothers of infants and the lack of initiative and skills of posyandu cadres. The provision of information, motivation and skills needed by cadres and mothers of children under five are considered as one step in nutrition recovery. The purpose of this activity is to increase the knowledge and skills of cadres and mothers of toddlers. Nutrition training was given to cadres and mothers of toddlers, namely measuring nutritional status, feeding infants and children, breastfeeding practices, detection of growth and development of nutrition recovery at the posyandu level. The results of this activity indicate that there is an increase in the knowledge of cadres and mothers of infants, at pretest 10% of knowledge is good and 5% of knowledge is lacking and at the time of posttest it is 85% of knowledge is good and 15% is sufficient. In addition, there was an increase in the skills of cadres and mothers of toddlers, at pretest 75% of their skills were sufficient and 25% of their skills were lacking and at posttest they were 90% of good skills and 10% were sufficient. Thus it can be concluded that there is an increase in the knowledge and skills of cadres and mothers of toddlers to be mostly good. Posyandu cadres and toddler mothers are expected to be able to carry out nutritional recovery at the follow-up phase at the posyandu level. Keywords: knowledges, skills, posyandu cadres, children under five mothers, nutrition recovery